Molecular characterization of monochloroacetate-degrading arthrobacter sp. Strain d2 isolated from Universiti Teknologi Malaysia agricultural area - Alomar, Duha; Abdul Hamid, Azzmer Azzar; Khosrowabadi, Elham; Gicana, Ronnie G.; Lamis, Robert J.; Huyop, Fahrul Zaman; Tengku Abdul Hamid, Tengku Haziyamin (Taylor & Francis, 2014)
Arthrobacter sp. strains D2 and D3 and Labrys sp. strain D1 capable of degrading 20 mM monochloroacetic acid (MCA) were isolated from soil contaminated with herbicides and pesticides. All three isolates were able to grow onMCAas the sole source of carbon and energy with concomitant chloride ion release in the growth medium (19 mM). Strains D2 and D3 (cells doubling time 7±0.3 h) grew four times faster than D1 (26±0.1 h). Strain D2 was then further investigated and could also grow in 10 mM of monobromoacetic acid (MBA),2,2-dichloropropionic acid (2,2DCP), D,L-2-chloropropionic acid (D,L2CP), L- 2-chloropropionic acid (L-2CP), D-2-chloropropionic acid (D-2CP), and glycolate as the sole sources of carbon and energy. Dehalogenase gene amplification using group I primers revealed a 410-bp polymerase chain reaction (PCR) product, but there was none using group II primers. The partial amino acid sequence analysis of group I DehD2 dehalogenase showed at least 32% identity to the corresponding regions of DehE, DhlIV, DehI, and D,L-DEX, with key amino acid residues Ser188, Ala187, and Asp189. These amino acid residues were involved in substrate binding and catalysis and were conserved in the partial amino acid sequence.